2014
DOI: 10.1080/17452007.2014.892472
|View full text |Cite
|
Sign up to set email alerts
|

Organising design in the wild: locating multidisciplinarity as a way of working

Abstract: The workplace ecology of a multidisciplinary design team is studied to better understand how design work is organised in the wild. Reported is an ethnographic account of the events and practices that were seen, in patterned and subtle ways, to organise the design work for a project. Design events and activities were distributed in nested contexts throughout the office setting. The design work was seen to be planned, self-organised and coordinated through a series of practical actions and events that occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…As also mentioned in the theory section, the aspects of flexible working and agile workspaces, which are important elements in shared space and one of the key elements from the workshop, are described by a number of authors such as (Luck, 2015), (Bell & Anderson, 1999) and (Hewitt, 1997), not to mention the many guides on designing open space offices from for example (Duffy, Craig, & Gillen, 2011) and many others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As also mentioned in the theory section, the aspects of flexible working and agile workspaces, which are important elements in shared space and one of the key elements from the workshop, are described by a number of authors such as (Luck, 2015), (Bell & Anderson, 1999) and (Hewitt, 1997), not to mention the many guides on designing open space offices from for example (Duffy, Craig, & Gillen, 2011) and many others.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last couple of decades an increasing amount of literature has been published on the topic of shared space in the workplace, with (Duffy & Powell, 1997) describing "The new office", (Khamkanya & Sloan, 2009) writing on flexible working and shared workspace and (Luck, 2015) writing on co-location for design work. Following from the space management approach, agile working and the field of workplace management provides insights in to how to manage an organisational change such as transitioning to shared space must be considered to be (Bell & Anderson, 1999).…”
Section: Workplace and Space Managementmentioning
confidence: 99%
“…Errors in contract documentation have been identified as a major cause of disputes within construction projects (Lopez & Love, 2012;Love, Cheung, Irani, & Davis, 2011). Luck (2015) recommended the co-location of multidisciplinary design teams in order to improve the design coordination process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that there is a need for organisations to be more concerned about how to create spaces for interaction (Paludan, 2010;Luck, 2014). This is supported by Hatch and Cunliffe (2012) who indicate 'loose ends' in organisation theory concerning learning, knowledge management and identity in relation to organisational culture and physical structure (p. 303).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of investigating space has been seen in different settings such as office layout (Grangaards, 2009;Leonard, 2012;Luck, 2014), urban spaces (Munro and Jordan, 2013) spaces in the educational sector (Oblinger, 2006;Nussbaumer, 2014). More and more international companies use physical space as a way to enhance creativity, create change and stimulate interaction among employees (Kristensen, 2004;Doorley and Witthoft, 2012).…”
Section: Introductionmentioning
confidence: 99%